High Efficient Numerical Simulation of Infrared Radiation from a Hot Exhaust Nozzle (Communications in Computational Physics, 2020)
A coupled model, capable of simulating transonic flow, solid heat conduction, species transport, and gas radiation, is developed that provides better computational treatment of infrared radiation from hot exhaust nozzles. The modeling of gasradiation is based on a statistical narrow-band correlated-k analysis, whose parameters are deduced from the HITEMP line-by-line database. To improve computationalefficiency, several methods are employed. A mixed analytical-numerical algorithm isdescribed for the stiffness of the two-equation turbulence model and an alternatingdirection implicit pretreatment for the ill-conditioned matrix appearing in the coupledproblem of flow and solid heat conduction. Moreover, an improved multigrid methodand a symmetry plane treatment of the radiation transfer-energy equations are also introduced. Four numerical simulations are given to confirm the efficiency and accuracyof the numerical method. Finally, an account of the aerothermodynamics and infraredcharacteristics for two types of nozzles are presented. The infrared radiation intensityof the Chevron ejecting nozzle is clearly smaller than that of the common axisymmetricejecting nozzle. All computations can be performed on a personal computer.